Interpersonal Mindfulness, Intergroup Anxiety, and Intercultural Communication Effectiveness Among International Students Studying in Russia - Khukhlaev, Oleg; Novikova, Irina; Chernaya, Anna (Frontiers in Psychology, 2022)
In modern psychology, mindfulness is an important resource for psychological well-being and intergroup relations, but its role in intercultural communication effectiveness has not been sufficiently studied. This research aims to identify the interrelationship between interpersonal mindfulness, intergroup anxiety, and intercultural communication effectiveness among international students. The sample includes 337 (Mage = 22.93, SD = 3.11) international students (41.5% of females) from different countries studying in Russian Universities. Interpersonal mindfulness was measured using the Interpersonal Mindfulness Scale, Intergroup anxiety using ten items adapted from Stephan and Stephan and used in Gudykunst and Nishida, and Intercultural communication effectiveness using the eight items adapted from Gudykunst’s Perceived Effectiveness of Communication measure. Descriptive analysis, correlations, and mediation analyses were used to process the data. The research findings showed that interpersonal mindfulness has both a direct effect on intercultural communication effectiveness and a mediation effect on intercultural communication effectiveness through intergroup anxiety among the international students.